2016
DOI: 10.13048/jkm.16016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jaeumkanghwatang (JEKHT), a Polyherbal Formula on the Pharmacokinetics Profiles of Tamoxifen in Male SD Rats (1) - Single Oral Combination Treatment of Tamoxifen 50 mg/kg with JEKHT 100 mg/kg within 5 min -

Abstract: The objective of this study was to elucidate the effect of Jaeumkanghwatang (JEKHT) on the plasma concentration and pharmacokinetics of tamoxifen in combination therapy as a process of the comprehensive and integrative medicine against breast cancer. Methods: After 50 mg/kg of tamoxifen treatment, JEKHT 100 mg/kg was orally administered within 5 min. The plasma were collected at 30 min before administration, 30min, 1, 2, 3, 4, 6, 8 and 24 hrs after end of JEKHT treatment, and plasma concentrations of tamoxifen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…However, interactions with herbal products have not been established except for some restricted natural compounds; tamoxifen enhanced warfarin effects, and it is contraindicate that co-administration of tamoxifen and wafarin 28,29) . In our previous studies, we have been observed the possible interactions with Korean traditional polyherbal formulas; we observed that oral co-administration of Jaeumkanghwa-tang, a traditional yin-tonifying herbal medicine has been used for various oriental obstetrical and gynecological fields within 5 min did not critically influenced on the pharmacokinetics profiles of tamoxifen after single 38) and repeated 39) co-administration at dosage levels of 50mg/kg in tamoxifen and 100mg/kg in Jaeumkanghwa-tang, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…However, interactions with herbal products have not been established except for some restricted natural compounds; tamoxifen enhanced warfarin effects, and it is contraindicate that co-administration of tamoxifen and wafarin 28,29) . In our previous studies, we have been observed the possible interactions with Korean traditional polyherbal formulas; we observed that oral co-administration of Jaeumkanghwa-tang, a traditional yin-tonifying herbal medicine has been used for various oriental obstetrical and gynecological fields within 5 min did not critically influenced on the pharmacokinetics profiles of tamoxifen after single 38) and repeated 39) co-administration at dosage levels of 50mg/kg in tamoxifen and 100mg/kg in Jaeumkanghwa-tang, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…Until now, we have observed the possible interactions with Korean traditional polyherbal formulas; oral co-administration of Jaeumkanghwa-tang, a traditional yin-tonifying herbal medicine used for various oriental obstetrical and gynecological fields within 5 min did not critically influenced on the pharmacokinetics profiles of tamoxifen after single 40) and repeated 41) co-administration at dosage levels of 50 mg/kg in tamoxifen and 100 mg/kg in Jaeumkanghwa-tang, respectively. It was also demonstrated that single co-administration of Gamiondam-tang within 5 min and with 2.5 hr-intervals critically influenced on the oral bioavailability of tamoxifen through variable influences on the absorption and excretion of tamoxifen at dosage levels of GMODT 100 mg/kg and tamoxifen 50 mg/kg, can be influenced on the toxicity or pharmacodynamic of tamoxifen in our previous studies 42,43) .…”
Section: Introductionmentioning
confidence: 99%